Radiation Effects on Bismuth and Antimony Chalcogenide Thin-Film Elements: Structural, Electrical, and Optical Characterization - Omonov Bunyodjon Ulugbek ugli (Research Parks Publishing LLC, 2023)
The study investigates the effect of radiation on thin-film elements utilizing bismuth and antimony chalcogenides. Radiation-induced damage in such materials is of significant interest due to their promising properties for applications in optoelectronic devices. The research employed a series of experiments to examine the response of thin-film elements under various radiation conditions. Results demonstrate the impact of radiation on the structural, electrical, and optical properties of bismuth and antimony chalcogenide thin films, shedding light on their suitability for radiation-hardened devices.